ANÁLISIS DEL DESEMPEÑO LABORAL DEL PERSONAL QUE PRESTA SUS SERVICIOS EN LA URBANIZACIÓN CIUDAD EL VALLE BABAHOYO - RIVERA GUERRA, MARIA RUTH (2018)
479/5000 Currently, the Urbanizations are well known for their environmental status, safety, maintenance and excellent management, which influences job performance, which must meet objectives that contribute to achieving the results that the company proposes. For this reason, the purpose of this case study is to analyze the work performance of the personnel who provide services in the "Ciudad El Valle" Urbanization, in the city of Babahoyo.